A Novel Method for Real Time Bio-Medical Signal Transmission & Monitoring for Medical Healthcare - Bhuyar D L, Dr.Shinde U.B, Dr.Kureshi A.K (International Journal of Advanced Science and Technology, 2020)
India has need to access a specialist care and advice in rural and remote areas. Wireless communication System aims to fill up this gap. It is no longer required for the doctor to be physically present at the hospital center, as is the case with most of the existing telemedicine systems. One of the most widely used methods to test the human health condition is to measure his/her ECG. We will design and built a ECG monitoring system that can measure user’s ECG using wireless communication. Tele-medicine is the use for medical information Transmission from one place to another via E-media. Tele-medicine is a new technology which Addition of telecommunication and information Science for medical Monitoring purposes. It gives a new Path when the distance between the doctor & patient is significantly too far. In rural area in India this type of research system will work efficientlyKeywords: ECG, Heart Rate, Method of Monitoring, Need & Significance, Proposed Architecture